2010
DOI: 10.1111/j.1467-9922.2010.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Corrective Feedback in SLA: A Meta‐Analysis

Abstract: This study reports on a meta-analysis on the effectiveness of corrective feedback in second language acquisition. By establishing a different set of inclusion/exclusion criteria than previous meta-analyses and performing a series of methodological moves, it is intended to be an update and complement to previous meta-analyses. Altogether 33 primary studies were retrieved, including 22 published studies and 11 Ph.D. dissertations. These studies were coded for 17 substantive and methodological features, 14 of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
530
6
10

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 691 publications
(570 citation statements)
references
References 69 publications
24
530
6
10
Order By: Relevance
“…Engaging all groups in these tasks served to level the playing fi eld for comparisons between CF and no-CF groups and also to ensure that those receiving CF were at a similar level in their knowledge of the target feature. As Li ( 2010 ) argued, because the no-CF group, which engaged in the same instructional activities, served as a control group, any differences detected among the recast, prompt, and no-CF groups "must be due to the presence or absence of feedback" (p. 319).…”
Section: Form-focused Instructionmentioning
confidence: 99%
“…Engaging all groups in these tasks served to level the playing fi eld for comparisons between CF and no-CF groups and also to ensure that those receiving CF were at a similar level in their knowledge of the target feature. As Li ( 2010 ) argued, because the no-CF group, which engaged in the same instructional activities, served as a control group, any differences detected among the recast, prompt, and no-CF groups "must be due to the presence or absence of feedback" (p. 319).…”
Section: Form-focused Instructionmentioning
confidence: 99%
“…Through setting comprehensive variables, the results demonstrated that learners perceived implicit feedback better than explicit feedback; feedbacks given during foreign language contexts were more effective than second language context; native teachers tended to provide more effective feedback than other teachers or computers. However, there were still some factors suggested by Li (2010) that needed to be studied, such as learners' age, proficiency, classroom context and even interlocutor types.…”
Section: Observational Classroom Studiesmentioning
confidence: 99%
“…Results suggested that when the teaching focus was more on form and the function of recast was prominent, recast could lead to more learner responses and repairs; meanwhile the distributions of corrective feedback and learner uptake didn't necessarily depend on classroom contexts. Li (2010), conducting a meta-analysis to 33 primary studies, testified the effectiveness of corrective feedback. Through setting comprehensive variables, the results demonstrated that learners perceived implicit feedback better than explicit feedback; feedbacks given during foreign language contexts were more effective than second language context; native teachers tended to provide more effective feedback than other teachers or computers.…”
Section: Observational Classroom Studiesmentioning
confidence: 99%
See 2 more Smart Citations